Nanohybrid and microfilled composite resin in Class II restoration of permanent molar teeth (Bangabandhu Sheikh Mujib Medical University Journal, 2019)
The aim of this study was to compare the clinical performance of nanohybrid composite resin in Class II restorations placed with a one-step self-etch adhesive with that of microfilled composite resin of permanent posterior molar teeth. A total of 100 participants who received Class II restorations either with nanohybrid composite resin bonded with a single step self-etch adhesive or conventional microfilled composite bonded with a single step self-etch adhesive. All restorations were evaluated by using slightly modified USPHS criteria at baseline and after 3, 6 and 12 months. The results revealed that nanohybrid composite resin showed better clinical outcome than that of the conventional microfilled composite resin restorations in respect to retention and marginal adaptation at 12 months observation period. It can be concluded that nanohybrid is superior to conventional microfilled composite resin in respect to retention, and marginal adaptation of Class II restorations of permanent molar teeth.